1997
DOI: 10.1093/sleep/20.10.844
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Sleepiness and Sleep Habits of Australian Workers

Abstract: Excessive daytime sleepiness in the general community is a newly recognized problem about which there is little standardized information. Our aim was to measure the levels of daytime sleepiness and the prevalence of excessive daytime sleepiness in a sample of Australian workers and to relate that to their self-reported sleep habits at night and to their age, sex, and obesity. Sixty-five percent of all 507 employees working during the day for a branch of an Australian corporation answered a sleep questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
276
7
15

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(325 citation statements)
references
References 0 publications
21
276
7
15
Order By: Relevance
“…Background data for each group are set out in Tables 1 and 2. <<Insert Tables 1 and 2 Chen et al, 2002;Johns, 1992;Johns, 2000;Vignatelli et al, 2003;Violani et al, 2003) with scores exceeding 10 indicative of some form of sleep disorder (Johns & Hocking, 1997). The ESS contains eight items, which a participant has to score on a scale of 0 (would never doze off in this situation) to 3 (high chance of dozing off in this situation).…”
Section: Methodsmentioning
confidence: 99%
“…Background data for each group are set out in Tables 1 and 2. <<Insert Tables 1 and 2 Chen et al, 2002;Johns, 1992;Johns, 2000;Vignatelli et al, 2003;Violani et al, 2003) with scores exceeding 10 indicative of some form of sleep disorder (Johns & Hocking, 1997). The ESS contains eight items, which a participant has to score on a scale of 0 (would never doze off in this situation) to 3 (high chance of dozing off in this situation).…”
Section: Methodsmentioning
confidence: 99%
“…Patients were also divided into 4 quartiles of subjective sleepiness according to their ESS: "normal" (0-5), "non-sleepy" (6-9), "sleepy" (10)(11)(12)(13)(14), and "very sleepy" (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The latter 3 categories for sleepiness were compared with the reference category (i.e., "normal").…”
mentioning
confidence: 99%
“…He also completed the Epworth Sleepiness Scale (ESS), a test to identify degrees of sleepiness [18], with a score of 12. Investigations have shown that a score of 10 or 11 is considered to be the upper parameter for normal [19,20]. After these studies, the patient was discharged with a diagnosis of moderate OSAS (AHI=20/h) and a request of an oral evaluation.…”
Section: Methodsmentioning
confidence: 99%